Community Policing dalam Implementasi Perda Ketertiban Umum dan Ketentraman Masyarakat di Kawasan Wisata Pantai Pasir Jambak Kota Padang - Putri Maharani; Siska Sasmita (YASIN, 2026)
Problems of public order and community tranquility in the Pasir Jambak Beach tourism area, which is often misused for activities that contravene social and religious norms as well as the provisions of the Regional Regulation, highlight the need for a law enforcement approach that is not only repressive but also participatory through the concept of community policing. This study aimed to analyze the application of community policing in implementing the Perda on Public Order and Community Tranquility in the Pasir Jambak Beach area, to examine the roles and partnerships of formal and informal actors, and to identify supporting and inhibiting factors in its implementation. A qualitative approach with a descriptive method was employed through in-depth interviews, field observations, and documentation involving Bhabinkamtibmas, Satpol PP, Babinsa, village officials, LPM, Karang Taruna, Pokdarwis, local residents, and visitors to the tourist area. Data analysis referred to Fisher–Stewart’s community policing theory with indicators of community partnership, problem solving, and organizational transformation. The findings show that community policing at Pasir Jambak Beach has been implemented through cross-actor partnerships in patrols, environmental surveillance, public advisories, and the reporting of violations by community members; however, its implementation is not yet optimal. In terms of community partnership, collaboration has been established but remains situational and not yet sustainable; in terms of problem solving, the stages of scanning, analysis, response, and assessment have been carried out and have contributed to a reduction in the number of pondok baremoh, although they have not completely eliminated violative practices; whereas in terms of organizational transformation, no significant changes are evident in agency management, personnel systems, or the use of information technology. Supporting factors include community and local group involvement, the role of Bhabinkamtibmas, and interagency cooperation, while inhibiting factors comprise weak ongoing communication, limited resources, the role dilemma faced by Pokdarwis, low community activism, and strong economic interests among local residents. These findings underscore that strengthening sustainable, multi-actor partnership–based community policing is key to enhancing the effectiveness of enforcing the Regional Regulation on Public Order and Community Tranquility in tourist areas.